Best practices for corporate libraries - Kelsey, Sigrid; Porter, Marjorie J. (Santa Barbara, Calif. : Libraries Unlimited, 2011)
"In this book, experts in the field describe best practices based on their experiences in corporate libraries worldwide"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Corporate libraries -- Administration; Corporate libraries -- Case studies; Information resources management